Assessment of Static Plantar Pressure, Stabilometry, Vitamin D and Bone Mineral Density in Female Adolescents with Moderate Idiopathic Scoliosis - Cațan, Liliana; Cerbu, Simona; Amaricai, Elena; Suciu, Oana; Horhat, Delia Ioana; Popoiu, Călin Marius; Adam, Ovidiu; Boia, Eugen (International journal of environmental research and public health, 2020)
(1) Background: Adolescent idiopathic scoliosis (AIS) can be associated with vitamin D deficiency and osteopenia. Plantar pressure and stabilometry offer important information about posture. The objectives of our study were to compare static plantar pressure and stabilometric parameters, serum 25-OH-vitamin D3 and calcium levels, and bone mineral densitometry expressed as z-score in patients with moderate AIS and healthy subjects. (2) Methods: 32 female adolescents (idiopathic S shaped moderate scoliosis, main lumbar curve) and 32 gender and age-matched controls performed: static plantar pressure, stabilometry, serum 25-OH-vitamin D3 and calcium levels, and dual X-ray absorptiometry scans of the spine. (3) Results: In scoliosis patients, significant differences were recorded between right and left foot for total foot, first and fifth metatarsal, and heel loadings. Stabilometry showed a poorer postural control when compared to healthy subjects (p < 0.001). Patients had significantly lower vitamin D, calcium levels, and z-scores. Lumbar Cobb angle was significantly correlated with the z-score (r = −0.39, p = 0.02), with right foot fifth metatarsal load (r = −0.35, p = 0.04), center of pressure CoPx (r = −0.42, p = 0.01), CoP displacement (r = 0.35, p = 0.04) and 90% confidence ellipse area (r = −0.38, p = 0.03). (4) Conclusions: In our study including female adolescents with idiopathic S shaped moderate scoliosis, plantar pressure and stabilometric parameters were influenced by the main scoliotic curve.